Potentiality of Moringa oleifera against SARS-CoV-2: identified by a rational computer aided drug design method. Issue 16 (2nd November 2022) - Sen, Debanjan; Bhaumik, Samhita; Debnath, Pradip; Debnath, Sudhan
Abstract: Coronavirus disease 2019 (COVID-19) has created a global human health crisis and economic setbacks. Lack of specific therapeutics and limited treatment options against COVID-19 has become a new challenge to identify potential hits in order to develop new therapeutics. One of the crucial life cycle enzymes of SARS-CoV-2 is main protease (M pro ), which plays a major role in mediating viral replication, makes it an attractive drug target. Virtual screening and three times repeated 100 ns molecular dynamics simulation of the best hits were performed to identify potential SARS-CoV-2 M pro inhibitors from the available compounds of an antiviral plant Moringa oleifera. Three flavonoids isorhamnetin (1 ), kaempferol (2 ) and apigenin (3 ) showed good binding affinity, stable protein-ligand complexes throughout the simulation time, high binding energy and similar binding poses in comparison with known SARS-CoV-2 M pro inhibitor baicalein. Therefore, different parts of M. oleifera may be emerged as a potential preventive and therapeutic against COVID-19. Graphical Abstract: UF0001 Communicated by Ramaswamy H. Sarma